EFFECT OF MEASURING INTELLECTUAL CAPITAL ON INVESTMENT - Dr. Mezban Mohammed Farhan; Qaed Khalif Hamzah; Mohammed Ali Mahdi (Scholar Express Journals, 2023)
The concept of intellectual capital is one of the relatively recent concepts, and the measurement of intellectual capital is complex because it is intangible and not disclosed in the financial statements (financial accounting outputs), while the measurement of investment for assets depends on its measurement on the financial statements. In this research Intellectual capital and its impact on investment were measured, and the research included a sample of companies listed in the Iraq Stock Exchange and for a number of sectors. According to Excel program, the results show that there is a positive relationship between intellectual capital and investment.
Keywords: Intellectual Capital; Measuring Intellectual Capital